Research on structural parameters of loess and its experimental determination method - Wu, Xiao-Juan; Dang, Fa-Ning; Li, Jia-Yang (Frontiers in Built Environment, 2025)
The structure of loess is an important physical property indicator. Just like grain size, moisture content and density, it also affects the physical and mechanical properties of loess. Based on the definition of the constitutive degree index, the definition of structural parameters was redefined. And conventional triaxial shear tests were conducted on undisturbed soil samples and remolded soil samples with different moisture contents and different dry densities. Firstly, the deformation characteristics and strength changes of the soil samples were analyzed. Then, based on the definition of structural parameters, the structural change laws of the soil were analyzed. Finally, the relationships between the structural properties and soil moisture, grain size and density were analyzed, thereby verifying that the newly proposed definitions of the structural parameters are reasonable.